The Da'wah Through Social Media Youtube (Analysis of Da'wah Content in the Hikayat Podcast Budi Ashari Official Episode 26 Ngaji Kok Berantem: - - Iswan, Muhammad; Pirol, Abdul; Palammai, Efendi (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2026)
This study examines Islamic preaching through YouTube social media in the Hikayat Podcast Budi Ashari Official episode 26 entitled Ngaji Kok Berantem. The main issue of the research is the phenomenon of conflict and polarization of the community in the digital space and the role of preaching in responding to these conditions. This study aims to describe the characteristics of Budi Ashari's preaching language, identify the religious values ??conveyed, and analyze the relevance of the preaching message to the spiritual and social life of the community. The method used is content analysis with Norman Fairclough's critical discourse approach, which is directed reflectively to understand the deeper meaning of the preaching message. Data were obtained from podcast transcripts,, journals, and other supporting sources. The analysis was carried out in three stages: analysis of the preaching language, the meaning of preaching, and spiritual and social reflection. The results show that Budi Ashari's preaching language is communicative, narrative, and contextual, combining historical stories with contemporary realities. The religious values ??highlighted include knowledge, faith, piety, peace, concern, and respect for differences within the framework of Islamic brotherhood. In conclusion, the preaching delivered is relevant to the challenges faced by the community in the era of social media and contributes to building